Nicotinic acetylcholine receptors regulate growth hormone in pituitary somatotrophs of tigers - Lulu Liu; Shilong Yang; Longhui Chai; Shipei Zhang; Dan Liu; Haitao Xu; Yue Zhao; Shiyu Chen; Guangshun Jiang; Bin Li (Communications Biology)
Abstract The Felidae exhibits remarkable diversity in body size, with lengths ranging from 50 to 370 cm and weights from 1.1 to 423 kg. However, the underlying mechanisms driving this variation remain poorly understood. Here, we focused on the Siberian tiger (Panthera tigris altaica), the largest of the six extant tiger subspecies, and revealed the surprising expression of nicotinic acetylcholine receptors (nAChRs) in pituitary somatotrophs, which are crucial for regulating growth hormone (GH) secretion. Single-nucleus RNA sequencing of Siberian tiger pituitary cells exhibited the coexpression of CHRNA3, CHRNB4, and CHRNA5 genes in somatotrophs, a finding confirmed by electrophysiological experiments demonstrating the formation of functional nAChRs. Activation of these receptors elevated intracellular Ca2+ levels, thereby enhancing GH secretion in somatotrophs. Notably, nAChRs were absent in the pituitary glands of mice, domestic cats, and rats, both in early life and adulthood, despite high acetylcholine levels during early life. These results suggest that nAChRs in Siberian tiger somatotrophs play a pivotal role in GH release, offering new insights into the molecular mechanisms regulating body size in these terrestrial giants.